Marriage certificate of Thomas Sisom and Priscilla Smith Sisom - Sisom, Thomas; Sisom, Priscilla Smith, active 1693.
Quaker marriage certificate of Thomas and Priscilla Smith Sisom.
Negative photocopy of handwritten transcript produced with the permission of Henry Pleasants.
Brickmaker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Marriage records; Quakers; Brickmakers